Serum to Pleural Fluid Albumin Gradient to Differentiate Transudative and Exudative Pleural Effusion - Mohanty, Dr. L. K.; Ingole, Dr. Nishikant A.; Ambad, Dr. Ranjit S. (International Journal of Innovative Research in Medical Science, 2018)
A total 105 cases of pleural effusion,65 male and 40 females having different etiology were analysed for pleural fluid albumin gradient. The findings were analysed and compared with Lights criteria to differentiate exudates from transudate. The pleural fluid to serum albumin cut off value 1.2gm/dl to differentiate between exudates and transudate showed sensitivity of 95.50%. Specificity of 87.5%.Positive predictive value 97.70% and efficiency of 94.28%.